Who Defines “Correct English”? A Critical Discourse Analysis of English-Learning Content on TikTok - Nusaibah Al Mashuunah Abdullah; Alan Jaelani; Amalul Umam; Sa’adatul Ulya (Universitas Islam Negeri Palopo, 2026)
Despite the growing popularity of TikTok as a platform for English language learning, limited attention has been given to how language ideologies are embedded in its instructional content. This study investigates how “correct” English is represented in English-learning content on TikTok, particularly in relation to Standard Language Ideology and Native-speakerism. Using a qualitative design, this study analyzes Fairclough’s Three-Dimensional Critical Discourse Analysis to twenty-four videos produced by Antonio Parlati. The data consist of spoken utterances, captions, and on-screen texts that contain explicit and implicit evaluations of English usage. Fairclough’s Three-Dimensional Critical Discourse analysis framework is employed to examine the data at the textual, discursive-practice, and sosial-practice levels. The findings reveal that “correct English” is constructed through three main patterns: native-like English as a preferred model, natural or real-life English as a marker of appropriate usage, and explicit correction as a mechanism for distinguishing preferred forms from non-preferred forms. These patterns show that correctness is not represented only as grammatical accuracy, but native-speaker authority. The study concludes that TikTok English-learning content functions both as a source of practical language instruction and a digital space where dominant ideologies about English correctness are reproduced and circulated. These findings highlight the need for English teachers, learners, and content creators to critically engage with and evaluate the ideological assumptions embedded in social media-based language instruction.